2021
DOI: 10.1186/s40066-021-00336-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal genetic variation in Ethiopian barley (Hordeum vulgare L.) landraces as revealed by simple sequence repeat (SSR) markers

Abstract: Background Ethiopia is considered as center of diversity for barley (Hordeum vulgare L.) and it is grown across different agro-ecologies of the country. Unraveling population structure and gene flow status on temporal scales assists an evaluation of the consequences of physical, demographic and overall environmental changes on the stability and persistence of populations. This study was to examine spatial and temporal genetic variation within and among barley landrace samples collected over a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 80 publications
3
6
2
Order By: Relevance
“…Comparatively overall lower heterozygosity is obtained in all the regions, this may be due to the factor explained by the cleistogamy in barley that, the flower sheds its pollen before opening, forcing plants with this habit to be entirely autogamous, which can reduce the heterozygosity [ 55 ]. Our result is lower than the reported ranges observed from 0.594 to 0.662, and the expected 0.688 to 0.773 heterozygosity for Ethiopian barley landraces [ 33 ]. This is probably due to the source of genotypes and the samples included improved varieties, which are obtained in the lower heterozygosity ranges in our study.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…Comparatively overall lower heterozygosity is obtained in all the regions, this may be due to the factor explained by the cleistogamy in barley that, the flower sheds its pollen before opening, forcing plants with this habit to be entirely autogamous, which can reduce the heterozygosity [ 55 ]. Our result is lower than the reported ranges observed from 0.594 to 0.662, and the expected 0.688 to 0.773 heterozygosity for Ethiopian barley landraces [ 33 ]. This is probably due to the source of genotypes and the samples included improved varieties, which are obtained in the lower heterozygosity ranges in our study.…”
Section: Discussioncontrasting
confidence: 96%
“…Therefore, our results showed that the SNP markers were informative and polymorphic. The average and range values of polymorphism observed in the present study were lower than the reported range values of 0.474 to 0.652 with an average value of 0.552 in barley landraces [ 33 ], 0.34 to 0.83 with an average of 0.57 in barley collections [ 51 ]. Another study with Ethiopian durum wheat by Alemu et al [ 52 ] estimated the ranged value from 0.01 to 0.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations